The Marine Fauna of New Zealand: Hexasterophoran Glass Sponges of New Zealand (Porifera: Hexactinellida: Hexasterophora): Orders Hexactinosida, Aulocalycoida and Lychniscosida. - Reiswig, H.M.; Kelly, M. (NIWA Biodiversity Memoir, 2011)
The Hexactinellida of New Zealand, orders Hexactinosida, Aulocalycoida, and Lychniscosida, are reviewed, inventoried from existing and new collections, and revised where necessary. Collections within the NIWA Invertebrate Collection and the Museum of New Zealand Te Papa Tongarewa, both in Wellington, and specimens from the NORFANZ mid-Tasman Sea survey housed at the Queensland Museum, yielded well over 300 catalogued specimens, some of which are from the Australian EEZ. The previous list of four known species in New Zealand, Farrea occa Bowerbank, 1862, Euryplegma auriculare Schulze, 1886, Chonelasma hamatum Schulze, 1886, and C. lamella Schulze, 1886, has now been expanded to 30, including 21 new species, within 15 genera, one of which is new (Homoieurete n. gen.). The neglected family Auloplacidae (Schrammen, 1912) is resurrected. All four species previously known from New Zealand waters are well represented in the newly surveyed material. Five species known from elsewhere, Anomochone expansa Ijima, 1927, Aphrocallistes beatrix beatrix Gray, 1858, Lefroyella ceramensis Ijima, 1927, Periphragella elisae Marshall, 1875, and Psilocalyx wilsoni Ijima, 1927, but previously unknown in the New Zealand area, are reported and described, extending their distribution ranges. The 21 new species include six in Farreidae, seven in Euretidae, four in Tretodictyidae, two in Auloplacidae, one in Aulocalycidae, and one in Aulocystidae; the new genus Homoieurete belongs to Euretidae. One of the new species described here, Neoaulocystis cristata n. sp., has been recorded only near the Kingdom of Tonga, but is included here for the sake of a complete review of the genus. Similarly, two new species of the genus Anomochone collected on the NORFANZ voyage are found thus far only in Australian waters (northern Norfolk Ridge and Lord Howe Rise), but are included in this work for the sake of completeness of the review of the genus in this region. Similarly, two new species have been described from the Australian EEZ surrounding Macquarie Island, on Macquarie Ridge, and have been included here, as the species are also found in the New Zealand EEZ. The moderate number of washed-out specimens whose dictyonal skeleton are incompatible with any known species in New Zealand waters indicates that several species remain unknown and are yet to be collected in condition needed for full species level determination and description.